A suicide research agenda for people from immigrant and refugee backgrounds. Issue 8 (14th September 2017) - Colucci, Erminia; Too, Lay San; Minas, Harry
ABSTRACT: The aim of this study was to establish mental health and suicide research priorities for people from immigrant and refugee background in Australia. This article focuses on the data relevant to the development of the suicide research agenda. This study was conducted using Delphi consensus method with two rounds of online questionnaires. A total of 138 and 86 participants, respectively, completed the first and second rounds of survey. Participants were policy makers, service providers, academics, service users, and carer advocates in Australia with expertise in mental health and/or suicide among people from immigrant and refugee backgrounds. Of the total 268 research questions included in the questionnaires, 70 questions about suicide were ranked as essential by over 50% respondents (i.e., the set level of consensus). In particular, research questions regarded as the greatest priority related to access and engagement with suicide prevention services, suicide protective and risk factors compared to populations not from immigrant and refugee backgrounds, and culturally appropriate assessment of suicide risk.